Effect of alkali treatment on physicochemical and microstructural properties of false banana fiber - Chalachew Nigussie Checol; Zenamarkos Bantie Sendekie (Scientific Reports)
Abstract False banana fiber (FBF) has recently been the subject of much research due to its potential use as a reinforcing material in the construction industry. The surface characteristics of FBF (roughness and hydric properties) significantly affect its adhesion to a matrix due to the presence of weak components. This study aims to enhance the performance of FBF, specifically its tensile strength and water absorption, and explore the microstructural changes brought about during alkali treatment by sodium hydroxide (NaOH) at concentrations of 3, 5.5, and 8 w/v%, at temperatures of 50, 70, and 90 °C, and treatment durations of 30, 45, and 60 min. The fiber’s tensile strength and water absorption, and interactions of independent variables were analyzed using response surface methodology (RSM). Furthermore, the physicochemical and microstructural characteristics have been studied. The optimum treatment conditions were 6.3% alkali concentration, 80.6 °C, and 60 min, at which the tensile strength was improved by 26% (from 615.37 to 775.24 MPa) and the water absorption was reduced by 68% (from 209.36 to 68.67%). The cellulose content was augmented by 35%, and the hemicellulose, lignin, and extractives were meaningfully reduced by 59, 55, and 68%, respectively. Consequently, alkali treatment significantly influenced the fiber’s tensile strength and water absorption properties, suggesting its potential for enhancing the fiber’s performance. Methods of characterization like fourier transform infrared (FTIR) spectroscopy, thermogravimetric, and scanning electron microscope (SEM) analyses provided valuable insights into the structural and thermal properties of the fibers, further supporting the potential of the fiber for engineering applications.